التقاطب المكاني و دلالاته في رواية "أصابع الاتهام" لجميلة زنير - تقار, فوزية (جامعة الوادي - University of Eloued, 2021)
يشكل التقاطب المكاني في الرواية عنصرًا مهما يلجأ إليه الروائي ليبرز المعنى و يوضحه في ذهن المتلقي؛ لأن المكان ليس بحامل لمعنى واحد، بل هو وعاءٌ يحمل دلالات نفسية و اجتماعية و أيديولوجية، كما تساعد التقاطبات المكانية على فهم كيفية ترتيب العناصر السردية الأخرى، فهو نبض الرواية و إيقاعها وبه يسير العمل الروائي بشكل متسلسل و متتابع. وبناءً على ذلك اخترنا رواية "أصابع الاتهام" لجميلة زنير للدراسة والتحليل لكونها مكثفة بالأماكن المغلقة و المفتوحة مثل: (القرية، المدينة، البيت، الشارع و المقبرة)، حيث اهتمت الكاتبة بالثنائيات المكانية المتقابلة بأفق دلالي مغاير، جنحت من خلالها إلى استنطاق الأعراف و التقاليد البالية التي تحدد أشكال الوعي المهيمنة في بيئة تمارس سلطتها على الآخر المختلف جنسيًا/ الأنثى، سعيًا منها إلى تجسيد مشاعر الإنسانية في أسمى معانيها. Abstract: The spatial polarity in the novel is an important element that the novelist uses to highlight the meaning and clarify it in the mind of the recipient. The place does not bear a single meaning, but rather a container that carries psychological, social and ideological connotations. Spatial polarizations also help to understand how the other narrative elements are organized and operated, as it is the pulse and rhythm of the novel, and with it the novel work proceeds sequentially and consecutivelly. Accordingly, we chose Jamila Zanir's novel "The Finger of Accusation" because it is full of closed and open places such as: (the village, the city, the house, the street, and the cemetery) where the author is concerned with the opposing spatial binaries with a different semantic horizon. Through it, it tended to interrogate the norms and traditions that define the dominant forms of consciousness in an environment that exercises its authority over the different sexually / female, seeking to embody the feelings of humanity in its highest meanings.
مقال
Keywords: التقاطب، المكان، الدلالة، أصابع الاتهام، الرواية، جميلة زنير.